2000
DOI: 10.1016/s0732-3123(00)00025-0
|View full text |Cite
|
Sign up to set email alerts
|

Objects, Actions, and Images: A Perspective on Early Number Development

Abstract: It is the purpose of this paper to present a review of research evidence that indicates the existence of qualitatively different thinking in elementary numberdevelopment. In doing so the paper summarises empirical evidence obtained over a period of ten years. This evidence first signalled qualitative differences in numerical processing (Gray, 1991), and was seminal in the development of the notion of procept (Gray & Tall, 1994

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Then counting the added units gives the answer, or, by keeping track of the number of words added/counted on the smaller given quantity (addend). Gray, Pitta and Tall (2000) conclude from multiple observations that children who are less able to solve arithmetic problems seem to rely extensively on counting procedures. Children who are skilled arithmetic problem solvers, on the other hand, seem to find plausible procedures almost intuitively (like the inverse relation between subtraction and addition).…”
Section: Strategies In Arithmetic Problem Solvingmentioning
confidence: 99%
“…Then counting the added units gives the answer, or, by keeping track of the number of words added/counted on the smaller given quantity (addend). Gray, Pitta and Tall (2000) conclude from multiple observations that children who are less able to solve arithmetic problems seem to rely extensively on counting procedures. Children who are skilled arithmetic problem solvers, on the other hand, seem to find plausible procedures almost intuitively (like the inverse relation between subtraction and addition).…”
Section: Strategies In Arithmetic Problem Solvingmentioning
confidence: 99%
“…Studies focused on imagery and arithmetic have indicated that students who recognise the structure of mathematical processes and representations acquire deep conceptual understanding (Pitta-Pantazzi, Gray & Christou, 2004;Gray, Pitta, & Tall, 2000;Thomas & Mulligan, 1995). Students with lower numerical achievement reported descriptive and idiosyncratic images; they focused on non-mathematical aspects and surface characteristics of visual cues.…”
mentioning
confidence: 99%
“…Successful Nonverbal Calculation gives insight into the child's quantitative representations without the intervening variables of language (as occurs in Story Problems) and Number Combinations which may have been developed by rote (see below); it is an ability that typically precedes both (Levine, Jordan, and Huttenlocher 1992). Nonverbal Calculation is an important achievement because it marks some understanding of 'counting-on' and 'counting-back' and an appreciation of counting as an abstract activity (Gray, Pitta, and Tall 2000).…”
Section: Nonverbal Calculationmentioning
confidence: 99%
“…Modelling may begin with manipulatives or pictorial referents to represent quantities (Lesh, Post, and Behr 1987) through 'seeing' quantities in one's head (Gray, Pitta, and Tall 2000) to principle-based reasoning where repeated opportunity to derive new number knowledge allows learners to construct their own rules and generalisations Baroody, Bajwa, and Eiland 2009;Palm 2008). A child at an early representational stage of modelling with manipulatives may find it difficult to simultaneously consider the relationship (Thompson 1993) indicated in the particular Story Problem's structure (Riley, Greeno, and Heller 1983).…”
Section: Story Problemsmentioning
confidence: 99%